Activity modulated low platium content oxygen reduction electrocatalysts prepared by inducing nano-order dislocations on carbon nanofiber through N-2-doping - Palaniselvam, Thangavelu; Irshad, Ahamed; Unni, Bipinlal; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
We demonstrate how surface unsaturation developed during small order buckling of graphene interlayer upon doping iron nitride (i.e., FeNx) moieties in carbon nanofiber can be utilized as a very efficient mode of surface activation to establish fine distribution of Pt nanoparticles with 10 wt %. The surface dislocations have been effectively modulating the oxygen reduction characteristics of Pt through synergistic effects of the interacting species. The simultaneous enhancement of dispersion of Pt and oxygen reduction reaction (ORR) activity with a low weight percentage of dispersed Pt has been attained by FeNx doping, which increases the density of the active sites owing to the formation of fine and abundant delaminated regions on the CNF surface. HR-TEM images clearly depict the fine distribution of Pt nanoparticles on the delaminated regions of FeNxCNF. The stable incorporation of Pt on nitrogen doped active sites has been further confirmed by observing the formation of Pt-N peak at 391.5 eV using XPS analysis. The fine distribution of Pt nanoparticles along the abundant nanopockets between the buckled graphene layers helped the system to attain significantly high electrochemically active surface area of Pt as evident from the cyclic voltammetric studies. The mass activity of PtFeNxCNF at 0.9 V vs RHE is 4.9 mA mgPt(-1) which is two times higher than that of E-TEK. The superior catalytic activity (exchange current density (i(0)) at 0.8 V is 2.61X 10(-6)) could be further confirmed by single cell evaluation of the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC), where the cathode electrode was fabricated from this new catalyst.